Retrospective analysis of efficacy of washed husband semen IUI for oligoasthenoteratospermia in an urban centre - Sivaraman, Shanthi; Eralil, Georgy Joy (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The true incidence of male subfertility is unknown due to great variability in the prevalence of subfertility. Artificial insemination with husband’s semen is the most widely used treatment for male infertility, usually presumed because of oligospermia, and for what is called ‘mucus hostility’ when there is failure of sperm penetration of cervical mucus despite normal seminal analysis. Methods: The study was conducted in 438 couples with male factor infertility at the ARTC (artificial reproductive technique centre) of Sri Ramakrishna Hospital, Coimbatore. Results of at least two seminograms (based on WHO norms) were used to primarily classify males into three categories-oligozoospermic, asthenozoo spermic and oligoasthenoteratospermic. The media used were the Earle’s Balanced Salt Solution (EBSS), Ham’s F10 and Medicult. EBSS and Ham’s F10 were obtained as “readymade” solutions from Sigma, USA. Medicult was imported from Denmark. EBSS and Ham’s F10 were supplemented with protein using FCS (Fetal cord Serum) or HEPES (4(2-hydroxyethyil)-1-piperazineethanesulfonic acid). Benzyl pencillin, 60mg per litre and Streptomycin, 50mg per litre were also to the media. Results: By the DMRT analysis of post wash count, the influence of the count below 5 million or above 20 million on the pregnancy rate was significant at all the levels of male factor. Conclusions: Considering the male factor, in cases of oligoasthenoteratospermia, IUI has a positive significant effect on the success rate of pregnancy at all three levels of the post wash sperm count.